Analisis Interferensi Bahasa Dalam Film Detective Conan Kurogane No Submarine Aoyama Gosho - Satrio, Rianto Dwi; Aryanto, Bayu (KIRYOKU, 2025)
Language interference is a language error that can occur in everyday life, both consciously and unconsciously. There are various types of interference, including lexical, phonological, morphological, and syntactic. It can also be seen as code switching which combines two or more languages in one sentence. This error affects communication with both positive and negative impacts. Various factors, such as mother tongue, translation, and language acquisition can cause interference. This study uses a qualitative quantitative method to collect data categorized by the type of interference, as seen in the Detective Conan Movie by Aoyama Gosho.